Resonances and Dissociative Electron Attachment in HNCO - Zawadzki, M; Čížek, M; Houfek, K; Čurík, R; Ferus, M; Civiš, S; Kočišek, J; Fedor, J (Physical review letters, 2018)
In a combined experimental and theoretical study, we probe the dissociative electron attachment in isocyanic acid HNCO. The experimental absolute cross section for the NCO^{-} fragment shows a sharp onset and fine structures near the threshold. The autoionizing state responsible for the dissociative attachment is found in both the R-matrix calculation and using analytic continuation in the coupling constant. The involved A^{'} resonance has a mixed π^{*}/σ^{*} character along the dissociating bond and thus combines the effects of nonzero electron angular momentum and dipole-supported states. This leads to unusual behavior of its width at various geometries. Because the potential energy gradient of the autoionizing state points essentially in the direction of the N─H bond, nuclear dynamics can be described by a one-dimensional nonlocal model. The results agree with the experiment both quantitatively and qualitatively. The present system may be a prototype for interpretation of the dissociative electron attachment process in a number of other polyatomic systems.